TOTAL PHYSICAL RESPONSE (TPR) METHOD THROUGH TIKTOK AS A LEARNING MEDIA TO IMPROVE STUDENTS’ LISTENING SKILL AT SMAN 18 MAKASSAR - Pare Datu, Virgina A.; Fansury, Andi Hamzah; Muliati, Muliati (Publikasi dan UKI Press UKI Toraja., 2023)
This study aimed to determine the use of the Total Physical response method (TPR) through tiktok as a learning media to improve students' listening skill at SMAN 18 Makassar. The research used pre-experimental research method. The population of this research was eleventh grade students of SMAN 18 Makassar at first semester academic year 2023/2024. The number of the sample were 33 students. The research collected the data by giving pre-test, treatment, and post-test. The data of this research was analyzed by SPSS 25 version. The researcher concluded that there was a significant improvement in students' listening skills by using the Total Physical Response (TPR) Method through Tiktok as a learning medium. This is supported by the results of the average scores in the pre-test and post-test. The average score on the pre-test was 55.45, while on the post-test was 84.70. The significant value in this study is 0.000 which is smaller than 0.5. This means that there is a significant improvement in students' listening skills with the Total Physical Response (TPR) Method through Tiktok as a Learning Media